DV AQUARII REVISITED - Polubek, G. (Одеські астрономічні публікації, 2017)
This work presents a new solution for the close binary system DV Aqr (HD 199603, HR 8024) based on archival International Ultraviolet Explorer observations, ground-based photometric light curves and radial velocity data. The solution is obtained as the best t of the theoretical model to all these observations simultaneously. Roche geometry of the binary system is assumed and a grid of the newest Kurucz models of stellar atmospheres is used in the calculations.